Comparing the Prevalence of Depression in Postmenopausal Women With and Without Urinary Incontinence - Mandana Mansour Ghanaie; Elaheh Abdolahi; Ehsan Kazemnezhad Leili; Roghayeh Hojat Ansari; Seyed Mohammad Asgari Galebin (Guilan University of Medical Sciences, 2020)
Introduction: Urinary incontinence is a common disorder that often affects the elderly. The prevalence of depression in people with urinary incontinence varies from 20-40%. Objective: This study aimed to investigate and compare the prevalence of depression in postmenopausal women with and without urinary incontinence. Materials and Methods: This comparative study with cross-sectional design was, conducted on 284 postmenopausal women in two groups of with and without urinary incontinence (controls). After recording their demographic characteristics, they all completed the Beck Depression Inventory-II (BDI-II). Chi-square, Mann-Whitney U test and logistic regression were used to assess depression score and severity of depression. Results: The mean age of participants was 57.62±9.62. The mean score of depression in women with urinary incontinence was higher than in the control group (8.85±7.35 vs. 6.11±5.03), and this difference was significant (P=0.001). According to the Chi-square test, the probability of depression in women with urinary incontinence was two-fold higher than that of controls (21.3% vs. 9.86%). Using logistic regression and controlling the effects of socio demographic variables, the odds of depression in women with urinary incontinence were 2.5 times higher than the control group (P=0.01). Conclusion: Depression and urinary incontinence in postmenopausal women are seemed to be related to each other. It is recommended that depression be screened in postmenopausal women with urinary incontinence